Severity and Factors Associated with Depressive Symptoms Among Type 2 Diabetic Patients in Vietnam - Nguyen, Kien; Nguyen Phuong, Hoa; Van den Broeck, Kris; Wens, Johan (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Background. Diabetes and psychiatric disorders often co-occur. The prevalence of depression in a person with diabetes is two times higher than that of the general population. During the last decade, the prevalence of diabetes in Vietnam has nearly doubled. However, there is little data regarding depressive symptoms among people with diabetes. Therefore, this study aims to explore the level of depressive symptoms and its associated factors among patients with type 2 diabetes mellitus in Hanoi, Vietnam. Methodology. A cross-sectional study was conducted among 519 patients diagnosed with type 2 diabetes at the Agricultural General Hospital, one of the largest primary care hospitals for diabetes in Hanoi, Vietnam. Patient Health Questionnaire-9 (PHQ-9) was used to assess the severity of depressive symptoms. Multivariate Tobit and logistic regression models were applied to examine factors associated with the severity of depressive symptoms and medication adherence Results. Approximately 45.2% of participants were identified as having depressive symptoms at different levels. The proportion of patients with mild, moderate, moderately severe, and severe depressive symptoms is 36.0%, 7.6%, 1.4%, and 0.2% respectively. Regarding the treatment process, patients being treated for their diabetes for a longer time were more likely to have depressive symptoms. DDepression was positively linked to currently drinking alcohol (Coef = 1.04; 95% CI = 0.30-1.78), having comorbidities (Coef = 1.08; 95% CI = 0.15; 2.01) and having irregular physical activities (Coef = -1.28; 95% CI = -2.18; -0.38). Patients with severe depressive symptoms (higher PHQ-9 score) were more likely to be non-adherent to their medications in the last month (AOR = 1.30; 95% CI = 1.17; 1.46). Conclusion. Our study shows that a high percentage of patients with diabetes have depressive symptoms. There is a strong association between having depressive symptoms and non-adherence to medications in the last month. To reduce the risk of developing depressive symptoms, depression should be screened at the initial treatment process and patients should be advised to avoid alcohol and to engage in physical activities regularly.